A comprehensive review of future thermal management systems for battery-electrified vehicles. (October 2020) - Jaguemont, Joris; Van Mierlo, Joeri
Highlights: Review of existing thermal management systems. Comprehensive outlook of future thermal management systems. Critical aspects highlighting the difference between the existing and advance thermal management systems. Detailed description of the integration of thermal management systems for automotive applications. Abstract: Heat management is an important issue during the operation of a Li-ion battery system resulting from the high sensitivity to temperature. Nowadays, a battery thermal management system (BTMS) is employed to keep the batteries temperature in range. In a modern battery, electrified vehicles (BEVs), two types of cooling systems are employed generally separately: active and passive systems. Nonetheless, the trend in thermal management aims to improve the battery pack design to reach longer autonomy or faster charging time. However, to address these future thermal challenges, future thermal management systems are required instead of the traditional BTMSs such as air cooling or liquid cooling. However, future BTMSs has not yet been documented. Therefore, this study gives an overview of the future BTMS starting with information on the effect of temperature on LiBs in terms of high-temperature, low-temperature and safety issues. Following, the advantages and disadvantages of the existing BTMSs, which are currently used to maintain the temperature of the batteries in a safe range are exposed. Finally, the progress made on the future battery thermal management systems and their ability to overcome the future thermal challenges is reviewed. In the end, a comprehensive review classifying comparatively the existing and upcoming battery management systems is proposed, which can be seen as a first look into the future BTMSs for automotive applications.